Raspberry-Pi Zero-Based Reflection Seismic Logger Design with Network Time Protocol Synchronization - Suparno, Supriyanto; Notonegoro, Hamdan Akbar; Wicaksono, Britantyo; Akbar, Abdurrahman Azzam (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2022)
Indonesia is a country with very high mineral reserve potential. The mining sector also contributes to non-tax state revenue. Efforts to explore the content of minerals in the earth's bowels can use the seismic reflection method. This seismological principle relies on the propagation of mechanical waves whose reflections are captured and recorded using a geophone. Limitations of domestically produced seismic instrumentation can slow down exploration activities.For this reason, developing domestic geo-seismic acquisition instrumentation is necessary to support exploration activities. In this study, eight units of a Raspberry Pi-based reflection seismic logger prototype device have been made using the MEMS ADXL355 accelerometer sensor with NTP protocol synchronization. Data from the initial test results show that the eight seismic reflection loggers of the device can work simultaneously in reading the seismic waves they receive.